The right to health in international law - Tobin, John (John William), 1968- (Oxford : Oxford University Press, 2012)
Lack of access to health care is one of the fundamental problems facing people in both developing and developed countries. This text examines the history, foundation, and meaning of the right to health in international law.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Medical laws and legislation, International; Health services accessibility -- Law and legislation